Effects of drought stress on the seed germination and early seedling growth of the endemic desert plant Eremosparton songoricum (Fabaceae) - Guan, Kaiyun; Li, Haiyan; Liu, Huiliang; Li, Xiaoshuang; Zhang, Daoyuan (Technische Universität Dortmund, 2013)
Eremosparton songoricum (Litv.) Vass. is an endemic and extremely drought-resistant desert plant with populations that are gradually declining due to the failure of sexual recruitment. The effects of drought stress on the seed germination and physiological characteristics of seeds and seedlings were investigated. The results showed that the germination percentage decreased with an increase of polyethylene glycol 6000 (PEG) concentration: -0.3 MPa (5 % PEG) had a promoting effect on seed germination, -0.9 MPa (15 % PEG)dramatically reduced germination, and -1.8 MPa (30 % PEG) was the threshold for E. songoricum germination. However, the contents of proline and soluble sugars and the activity of CAT increased with increasing PEG concentrations. At the young seedling stage, the proline content and CAT, SOD and POD activities all increased at 2 h and then decreased; except for a decrease at 2 h, the MDA content also increased compared to the control (0 h). These results indicated that 2 h may be a key response time point for E. songoricum to resist drought stress. The above results demonstrate that drought stress can suppress and delay the germination of E. songoricum and that the seeds accumulate osmolytes and augment the activity of antioxidative enzymes to cope with drought injury. E. songoricum seedlings are sensitive to water stress and can quickly respond to drought but cannot tolerate drought for an extended period. Although such physiological and biochemical changes are important strategies for E. songoricum to adapt to a drought-prone environment, they may be, at least partially, responsible for the failure of sexual reproduction under natural conditions.
EXCLI Journal ; Vol. 12, 2013
Keywords: drought stress; Eremosparton songoricum; physiological characteristics; seed germination; seedling growth; 610